MIE GACOAN'S CULINARY HEGEMONY IN MAKASSAR - Amsal, Bahrul; Mario, Mario; Jusnawati, Jusnawati (Universitas Negeri Makassar, 2024)
This article reviews the culinary franchise Mie Gacoan in the city of Makassar. As a brand, Mie Gacoan has captured the attention of the people of Makassar, especially students, college students, and families. The spicy flavor and affordable prices make its outlets popular among many visitors. The appeal of Mie Gacoan is also evident from the long lines of visitors also highlight Mie Gacoan's appeal. The Mie Gacoan outlet in Makassar, despite its crowded customer base, boasts comfortable seating, internet access, and an Instagram-worthy ambiance, attracting young people who use it as a destination for selfies and social media engagement. Mie Gacoan's success has had an impact on the Makassar people's culinary culture. Market expansion, which establishes six outlets, signifies a form of hegemony aimed at influencing the public's consumption preferences. This article's research method employs a qualitative descriptive approach in the form of written narratives based on data collected through interview instruments. The conclusion of this article is that, first, Mie Gacoan's dominance in Makassar represents a form of culinary power that has the potential to shift the culinary preferences of the Makassar people, who are rich in traditional cuisine. The strategy is to provide cheap products, leverage influencers, and create viral content. Secondly, Mie Gacoan, as an affordable food offering, poses a threat to the diversity and richness of Makassar's local culinary scene.